Public Administration Study Program Needs for Public Speaking Ability in English to Improve Graduate Quality - Dian Rahma Santoso; Lailul Mursyidah; Wahyu Taufiq (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to find the needs of the Public Administration Study Program related to Public Speaking to prepare graduates who are competent in speaking in public using English as a provision to face the global era. There is a desire and hope that graduates of the Public Administration Study Program have global competitiveness in addition to science related to administration. To maximize the potential of the next candidate for Public Administration graduates, a material design is needed to improve Public Speaking skills by first analyzing the Public Speaking skill needs that are most needed by the study program. This study analyzes the needs of expected materials from a semi-structured interview with the Head of the Public Administration Study Program. The results of the research show that the Public Administration study program wants to focus on learning objectives on improving communication skills based on the future job needs of graduates seen through tracer studies. Highlights: Effective Communication in English: Enhancing public speaking skills in English is crucial to prepare graduates for the global era and increase their international employability. Job-Oriented Learning Objectives: The study program aims to align public speaking materials with the specific needs of future jobs, identified through tracer studies, to make graduates more job-ready. Competency Beyond Administration: While the program focuses on administration knowledge, it also emphasizes developing well-rounded communication abilities, enabling graduates to excel in diverse professional settings. Keywords: Public Administration Study Program, Public Speaking, Global Competitiveness, Material Design, Communication Skills